Zinc fertilizer application improves growth, yield and profit of paddy (Oryza sativa L.) in a zinc deficient Inceptisol - Sucharita, Swati; Rautaray, SK; Satapathy, MR; Nayak, RK (ORYZA-An International Journal of Rice, 2023)
A field experiment was conducted at the Central Farm, Regional Research and Technology Transfer Station of Coastal Zone, OUAT Bhubaneswar in kharif 2021 to study the effect of zinc fertilizer application on growth, yield and income of rice in a zinc (Zn) deficient soil. The soil was sandy loam, acidic (pH 5.4), medium in organic carbon (0.61%) and available P (10.3 kg ha-1) while low in available N (155.4 kg ha-1) and K (82.1 kg ha-1). Eight treatment combinations comprising rate, source and method of Zn application were laid out in a randomized block design with 3 replications. The results revealed that soil application of Zn 5 kg ha-1 as basal followed by foliar spray of Zn @ 0.1% produced highest LAI (3.87), dry matter production (25.9 g hill-1), panicles m-2 (315.8), test weight (22.76 g), grain yield (4937 kg ha-1), and zinc content in grain (39.48 mg kg-1) and straw (55.87mg kg-1). However, application of Zn @ 5 kg ha-1 alone was at par with the soil application followed by foliar spray. Hence, it is concluded that soil application of Zn 5 kg ha-1 at the time of final land preparation along with the soil test based NPK is optimum for higher productivity and profitability of rice in zinc deficient Inceptisol.